EVALUATION OF MENTAL STATUS AND ITS CORRECTION AGOMELATINE IN PATIENTS WITH ACUTE CORONARY SYNDROME - T. M. Poponina; K. I. Gunderina; Yu. S. Poponina; V. A. Markov (Бюллетень сибирской медицины)
Continuous sampling method using aquestionnaireHospitalAnxiety and Depression Scale (GSHTD) held survey 250 patients with acute coronary syndrome (ACS) admitted to the emergency Department of cardiologyInstituteofCardiology, SB of RAMS. Of these, 85 people (34%) were detected symptoms of anxiety and depression in 165 people (66%), anxiety and depressive symptoms were found. In a pilot randomized prospective comparative study included 46 people. Against the background of the basic treatment of ACS, 23 patients received an additional agomelatine. Results of the study are showed an improvement in mental status and quality of life